Algorithmic Citizenship Awareness Formation in AI Shaped Democratic Learning Ecosystems - Hafidh Maksum; Anwar Anwar; Badratun Nafis; Maulidar Maulidar; Putry Julia (Pusdikra-Publishing.com, 2026)
The development of artificial intelligence (AI) technology has affected the way people obtain information, interact, and participate in the life of digital democracy. Algorithms that regulate the distribution of information across various digital platforms indirectly shape people's perceptions, attitudes, and civic participation. This condition requires civic education to be able to respond to changes in the learning ecosystem that are increasingly influenced by digital technology and algorithmic systems. This study aims to analyze the formation of algorithmic citizenship awareness in the democratic learning ecosystem influenced by artificial intelligence. The research uses a qualitative approach with literature study methods on various scientific sources related to civic education, digital literacy, and the development of AI technology in the digital public space. The results of the study show that digital algorithms have an important role in shaping patterns of political participation, access to information, and democratic awareness of citizens. Therefore, civic education needs to integrate digital literacy, algorithmic literacy, and critical thinking skills so that students are able to understand the impact of technology on the democratic process. Such integration is important to form adaptive, critical, and responsible citizens in the digital democracy ecosystem.